Multi-machine collaboration realization conditions and precise and efficient production mode of intelligent agricultural machinery - Wang, Bo; Du, Xiaoxue; Wang, Yana; Mao, Hanping (International Journal of Agricultural and Biological Engineering, 2024)
Multi-machine collaboration of agricultural machinery is one of the international frontier and hot research in the field of agricultural equipment. However, the current domestic multi-machine collaborative operation of agricultural machinery is limited to the research of task goal planning and collaborative path optimization in a single production link. In order to achieve the purpose of zero inventory of agricultural materials and precise and efficient production operations, a new technology of agricultural machinery multi-machine collaboration with multi-dimension and full chain was proposed, which takes into account the whole process of agricultural production, as well as agricultural machinery system and external supply chain, storage and transportation chain collaboration. The problems of data collaboration, process collaboration and organization collaboration were analyzed. And the realization conditions of new multi-machine cooperative technology were analyzed. Meanwhile, the zero inventory mode and precise operation mode of agricultural materials under the background of multi-machine cooperation of intelligent agricultural machinery were studied. Then, a precise and efficient agricultural production mode based on data-process-organization collaboration was constructed. The results showed that the multi-machine cooperative technology mode of multi-dimensional and full-chain agricultural machinery could greatly improve the efficiency of agricultural machinery, operation quality, land utilization rate and reduce production cost. Key words: intelligent agricultural machinery; multi-machine collaboration; multi-dimensional; whole chain; zero inventory; precise and efficient; production mode DOI: 10.25165/j.ijabe.20241702.8127 Citation: Wang B, Du X X, Wang Y N, Mao H P. Multi-machine collaboration realization conditions and preciseand efficient production mode of intelligent agricultural machinery. Int J Agric & Biol Eng, 2024; 17(2): 27–36.